Speleothem U-series constraints on scarp retreat rates and landscape evolution: an example from the Severn valley and Cotswold Hills gull-caves, UK - Farrant, Andrew R.; Noble, Stephen R.; Barron, A.J. Mark; Self, Charles A.; Grebby, Stephen (Geological Society of London, 2014)
Modelling landscape evolution requires quantitative estimates of erosional processes. Dating erosional landscape features such as escarpments is usually difficult because of the lack of datable deposits. Some escarpments and valley margins are associated with the formation of mass-movement caves, sometimes known as ‘gull’ or ‘crevice’ caves, which are typically restricted to within 0.5 km of the valley margin or scarp edge. As in other caves, these mass-movement cavities may host speleothems. As gull-caves develop only after valley incision, uranium-series dating of speleothems within them can provide a minimum age for the timing of valley excavation and scarp formation. Here we present data from several gull-caves in the Cotswold Hills, which form the eastern flank of the Severn valley in southern England. U-series ages from these gull-caves yield estimates for both the minimum age of the Cotswold escarpment and the maximum scarp retreat rate. This is combined with data from geological modelling to propose a model for the evolution of the Severn valley and the Cotswold Hills. The data suggest that the location of the escarpment and regional topography is determined not by valley widening and scarp retreat, but by the in situ generation of relief by differential erosion.